Voltage uprating of existing 275kV overhead transmission line tower for increasing the power transfer capability - Mat Yamin, Mohd Khairuddin (2012)
This project presents a methodological approach, suggestions and information in uprating the existing 275kV transmission overhead line. The work also calculate and analyses the effect of conductor swing angle on L3 tower top geometrics and keep the probability of flashover at low state. In this project, the insulator length and clearances of swing conductor to tower body, top cross-arm, bottom cross-arm and conductor to conductor are considered. The purpose of this work is to determine the clearances necessary to insulator withstand for 400kV line. In addition, it is also important to make sure that conductors have to maintain the clearances under TOV (temporary over-voltage), switching and lightning overvoltages. The work in this project have used Excel and Smart Draw to analyze the results and plot the clearance distances of swing conductor, also the phase to phase rms voltage and redrawing the existing overhead tower. Therefore, voltages rating for the L3 tower can be determined through the available clearances. Firstly, the voltage rating is determined with standard 400kV specification of insulator length. Then, the insulator is being shorted to do the analysis to the voltage rating and lastly, the overall cross-arm is changed to fully insulate such as composite cross-arm. As the result, by using standard insulator length, the tower only carried 351kV rather than composite cross-arm that carry 450kV. The standard L3 tower will be increase the power transfer capacity to 400kV in term of voltage by changing the steel cross-arm to composite cross-arm.